Effects of Self-Management Education on Self-Efficacy and Quality of Life in Patients with Ulcerative Colitis: A Randomized Controlled Clinical Trial - Mahboobeh Magharei; Sakineh Jaafari; Parisa Mansouri; Alireza Safarpour; Seyed Alireza Taghavi (Shiraz University of Medical Sciences, 2019)
Background: Self-management (SM) as a dynamic process enables Ulcerative colitis (UC) patients to live with this chronic illness. The present study aimed to investigate the effect of SM education on self-efficacy (SE) and quality of life (QoL) in patients with UC. Methods: This randomized controlled clinical trial study was conducted on 64 patients with UC from December 2016 to February 2017 at Motahari clinic, Shiraz. Patients were randomly divided into two groups of intervention and control. The education program included six 90-minute sessions in 3 weeks and one month telephone follow-up. Before, immediately and one month after the intervention, the participants filled out the Strategies Used by People to Promote Health (SUPPH) for SE, and the Inflammatory Bowel Disease Questionnaire-9 (IBDQ-9) for Qol. Then, data were entered into SPSS 18.0 and analyzed using independent samples t-test, Chi-square, repeated measures ANOVA and Pearson's correlation coefficient. Results: A significant increase was observed in terms of the overall mean score for SE and its dimensions in the intervention group (P<0.001). These scores were significantly higher than those of the control group (P<0.001), except for positive attitude (P=0.15). The scores for overall Qol and its dimensions significantly increased in the intervention group immediately and one month after the intervention (P<0.001), and the difference between the two groups was significant (P<0.001). There was a significant positive correlation between SE and Qol (r=0.32, P=0.01). Conclusion: SM improved the SE and Qol in patients with UC. SM educatoin is recommended in nursing care of patients with UC. Trial Registration Number: IRCT2016092429823N1